A silent sacrum in the painting of Stefan Gierowski - Jagnicka, Olga (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
The article focuses on the presence of the sacred in the works of Stefan Gierowski. The phenomenon of the presence of spirituality is analysed on the basis of several works belonging to the cycle Painting the Ten Commandments (1986–1987). The cycle originated as a visual interpretation of the Decalogue. The artist interprets the theme taken up through the language of form and colour, expressing his conviction that through the language of abstract art it is possible to fully depict the sphere of spirituality. I analysed selected four works from the cycle, in which, in addition to showing their relationship to the biblical Decalogue, the aspect of silence and contemplative experience was highlighted. Purity, clarity of compositions characterising Gierowski’s painting cycle is a artistic response to fundamental moral rights. The main objective of the article is to show how art can produce a contemplative experience and convey the value of silence in the modern man’s environment.